THE USE OF CARROT SEED OIL (DAUCUS CAROTA L.) TO FORMULATE NANOEMULGELS AS AN EFFECTIVE NATURAL SUNSCREEN AND SKIN ANTI-AGING - ARIANTO, ANAYANTI; BANGUN, HAKIM; SUMAIYAH; YANTI PUTRI SIREGAR, CHRISTY NATASYA DWI (International Journal of Applied Pharmaceutics, 2022)
Objective: The purpose of this study was to develop a nanoemulgel containing vegetable oil of carrot seed oil as an effective natural sunscreen and skin anti-aging. Methods: Nanoemulgels containing 4% carrot seed oil were formulated in three formulas with different ratios of Tween 80 and Sorbitol and prepared by using the high-energy emulsification method. The nanoemulgels were determined for the organoleptic characteristic, globule size, pH, physical stability during storage for 12 w at three different temperatures (room, high and low temperature), centrifugation, and cycling test. The Sun Protection Factor (SPF) value was determined by UV spectrophotometric method and the effectiveness of anti-aging was evaluated by using a skin analyzer and the results were compared with sunscreen emulgel. Results: Nanoemulgel containing 4% carrot seed oil with a ratio of Tween 80 as surfactant and Sorbitol as co-surfactant 40 and 20 resulted in the smallest mean droplet size of 338.34 nm and the sizes were increased during 12 w of storage at room temperature but still in the nano size and this nanoemulgel did not show phase separation or still stable. These nanoemulgels were also stable after the centrifugation and cycling test. The emulgel preparation was not stable or showed phase separation after the centrifugation test. The SPF value obtained from the nanoemulgel was 20.28±0.22 and these values were higher than the sunscreen emulgel (13.94±0.27). The pore size, spot, and wrinkles of the volunteer skin were reduced after using the nanoemulgel containing 4% carrot seed. Conclusion: The sunscreen and skin anti-aging activity of nanoemulgel preparation containing 4% carrot seed oil with a ratio of surfactant Tween 80 and co-surfactant Sorbitol 40 and 20 were more effective compare with emulgel preparation.